Analisis Biaya Terapi pada Pasien Infeksi Saluran Kemih Rawat Inap di RSUD Dr. Moewardi Surakarta pada Tahun 2016 - Windi Astuti; Gunawan Pamudji Widodo; Rina Herowati (Fakultas Farmasi Universitas Setia Budi, 2018)
Urinary tract infection is one of the infectious diseases that occur due to the presenceof microorganisms in the urine. Urinary tract infection financing was regulated in the INA-CBG’srates. The study purpose was determined the conformity of real cost to the INA-CBG’s rates inhospitalized of national health insurance patients with urinary tract infection disease in Dr.Moewardi hospital Surakarta in 2016.This study was an observational study using a cross sectional design. Retrospectivedata collection method. Data were analyzed to see the treatment pattern of patients duringhospitalization, to find the difference in real costs with INA-CBG's rates using the one sample ttest,and to see factors related to real costs using the bivariate correlation test.The result showed that the treatment pattern for hospitalized patients with urinary tractinfection are using Ceftriaxone (40,8%), Cefixime (7,1%), Ceftazidime (10,2%), Ciprofloxacin(26,5%), Levofloxacin (9,2%), Amoxicillin (3,1%), Ampicillin (1,0%), and Gentamicin (2,0%). Theanalysis of real cost to the INA-CBG’s rates showed the differences between real cost and INACBG’srate of national health insurance patients with urinary tract infection disease.This difference shows a positive condition, where the total real costs are lower than the INACBG'srates. The factor related to the real cost of urinary tract infection treatment including ofLOS, secondary diagnoses, and treatment classes.